RESPON PERTUMBUHAN VEGETATIF Pennisetum purpureum cv. GAMA UMAMI DENGAN DIAMETER STEK YANG BERBEDA - Sari, Devi Novita; Dianita, Rahmi; Alwi, Yun (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research aims to determine the vegetative growth in Gama Umami elephant grass, which is influenced by the diameter of stem cuttings. This research used a Completely Randomized Design (CRD) with different diameter treatments, namely, D1= of 1-1.2 cm (small), D2 = of 1.3-1.8 cm (medium), and D3 = of 1.9-2.2 cm (large). The results showed that the plants with large diameters emerged the first bud early compared to those with small and medium diameters. However, the plant with a small diameter had good initial growth, with the number of leaves increasing from the second week, followed by many buds, plant height, and leaves. In this study, it can be concluded that using a plant with a small diameter shows the best results, which can be seen from the number of buds, leaves, plant height, and area.